Strengthening the Character Education based on the Social Skills of Students in the Integrated Thematic Learning in Primary Schools - Safitri, Novia Faiz; Setyowati, Dewi Liesnoor; Khafid, Muhammad (Educational Management, 2019)
Strengthening character education is already widespread in primary schools, however, there are schools that have not optimized its implementation. The purpose of this study was to analyze the strengthening of character education based on social skills through the integrated thematic learning in Darussalam elementary school Semarang, consisting of planning, implementing and evaluating the strengthening of character education through the integrated thematic learning. The method used in this study was qualitative research with a phenomenological design. The data collection techniques was using in-depth interviews, observation and documentation. The data analysis techniques used were data collection, data reduction, data presentation and drawing conclusions. The results showed that the reinforcement of character education was carried out through three stages, namely planning which carried out by preparing and developing the characterized lesson plans, the second was implementation by linking the learning with monotheism and the stages of the five continuum, and finally the evaluation by using K13 attitude assessment and specific guidelines for monotheism assessment. The conclusion in this study was that the strengthening of character education is carried out through these three stages, each of which is implemented optimally by the school. The benefits of this study is that it is expected to increase the repertoire of knowledge and broaden insights about the social skills of elementary students in strengthening the character education through the learning activities.